Quality of life and cancer-related needs in patients with choroidal melanoma. Issue 11 (13th September 2013) - Wiley, Joshua F; Laird, Kelsey; Beran, Tammy; McCannel, Tara A; Stanton, Annette L
Abstract : Aims: To assess quality of life (QoL) indices and their associations with treatment modality, sociodemographics and cancer-related needs in choroidal melanoma patients. Methods: Patients (N=99) treated at the University of California, Los Angeles, for choroidal melanoma within the prior 5 years (M=2.05) completed questionnaires assessing demographics, cancer-related needs, vision-specific QoL, depressive symptoms and concern about recurrence. Visual acuity, comorbidities, treatment modality (radiotherapy, enucleation) and years since diagnosis were gathered from medical records. Primary analyses were multiple regressions. Results: Although concern about cancer recurrence was elevated, QoL was better than in other oncology samples and comparable with healthy samples on some outcomes. Enucleation was associated with worse vision-specific QoL, and presence of comorbid diseases was associated with worse vision-specific QoL, depressive symptoms and concern about cancer recurring (all p values<0.05). Patients who experienced at least one stressful life event in the past year (vs no events) reported more depressive symptoms (p<0.01). Report of more unmet cancer needs was associated with worse vision-specific QoL, depressive symptoms and more concern about recurrence (all p values<0.05), uniquely explaining 4%–12% of the variance. Conclusions: For choroidal melanoma patients, an average of 2 years after treatment, the number of physical comorbidities and unmet cancer needs were the strongest correlates of poorer QoL.